Officer of Land Forces’ Qualification Evaluation of Foreign Communication: Criteria and Indices - Mantsurovich, Bikbaev Vadim (International Journal of Psychosocial Rehabilitation, 2020)
The article concerns the structure of foreign language communication, and formation of its dual nature (criteria and indices of foreign language communication qualification evaluation are concerned). There are three sets of evaluation indices according to the criterion «ability» - instilling foreign language communication in an individual that is cognitive component concentrated on professional phenomenon person, their social experience and self-esteem. There is a character for the criterion «effectiveness of foreign language communication» and sets of evaluation indices for its using, as regards ability in doing professional foreign language communication. Mental processes and human language abilities are of great importance concerning learning foreign languages as they are the manifestations of nature psychophysiological is emphasized in the article. It is noted that an exact memory and ability to foreign language communication are interchangeable, on the one hand, memory has a great impact on learning foreign language, on the other hand, studying vocabulary and grammar materials extend the memory and has a fundamental impact on mental processes. The quality of professional experience is noted to explain by the correlation of the entrenched situations developed by the military science and practical ways of accomplishing communicative task on the new stage of professional growth of the officer of the Land forces.